2013
DOI: 10.3177/jnsv.59.178
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Excretion Levels of Water-Soluble Vitamins in Pregnant and Lactating Women in Japan

Abstract: Dietary habits of pregnant and lactating women have a critical impact on the health of future infants. For this reason, the Japanese Dietary Reference Intakes regarding the amounts of addition of water-soluble vitamins have been set (1). The additional intake amounts for pregnant and lactating women were calculated based on data concerning the changes in the metabolic characteristics of vitamins in pregnant women and the loss of vitamins as a result of lactation. However, there is little information about whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 59 publications
2
13
0
Order By: Relevance
“…We consider the amount of urinary excretion of water-soluble vitamins to reflect surplus intake of water-soluble vitamins (22). Our previous study results (20) suggest that the requirement of folate for pregnant women is lower than that of non-pregnant women, but this might not be the case because it is well known that a folate deficiency, macrocytic anemia, occurs in late pregnancy (23). A possible mechanism for the increase in urinary excretion of folate is increased absorption of folate during late pregnancy (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We consider the amount of urinary excretion of water-soluble vitamins to reflect surplus intake of water-soluble vitamins (22). Our previous study results (20) suggest that the requirement of folate for pregnant women is lower than that of non-pregnant women, but this might not be the case because it is well known that a folate deficiency, macrocytic anemia, occurs in late pregnancy (23). A possible mechanism for the increase in urinary excretion of folate is increased absorption of folate during late pregnancy (24).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, with the use of stable-isotope-labeled folate, no differences in urinary excretion of labeled folate or its catabolites between pregnant and non-pregnant women was reported (19). In our previous study, we reported that the urinary excretory level of folate was higher during pregnancy than in nonpregnant women (20). Folate concentration in our previous study (20) was measured by microbiological assay using Lactobacillus rhamnosus, ATCC 27773 (10,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a population of Caucasian women in the USA, Song et al (1985) observed a mean (± SD) pantothenic acid intake of 5.3 (± 1.7) mg/day during the third trimester of pregnancy (n = 26) and of 4.8 (± 1.6) mg/day in non-pregnant women (n = 17). In a study in Japanese women, Shibata et al (2013) reported mean ( ± SD) pantothenic acid intakes of 5.7 (± 2.1) mg/day (second trimester, n = 24) and 5.7 (± 1.7) mg/day (third trimester, n = 32) in pregnant women and 5.0 (± 1.5) mg/day in non-pregnant women (n = 37). In a cohort of 42 pregnant women in the UK, mean (± SD) pantothenic acid intakes of 3.7 (± 1.2) mg/day, 3.9 (± 1.2) mg/day, 3.9 (± 1.0) mg/day and 3.6 (± 1.1) mg/day during the first, second and third trimesters of pregnancy and six weeks post partum, respectively, were observed, using four-to seven-day weighed dietary records (Derbyshire et al, 2009).…”
Section: Dietary Intakesmentioning
confidence: 99%
“…Two small cohort studies in pregnant and lactating women and non-pregnant, non-lactating women provide data on pantothenic acid intakes as well as urinary pantothenic acid excretion (Song et al, 1985;Shibata et al, 2013) and whole blood pantothenic acid concentration (Song et al, 1985). Mean pantothenic acid intakes were between 5.3 and 6.2 mg/day in pregnant and lactating women and between 4.8 and 5.0 mg/day in controls.…”
Section: Specific Considerations During Pregnancy and Lactationmentioning
confidence: 99%